Une méthode d’homogénéisation pour l’analyse modale d’un problème d’interaction fluide/structure - Broc, Daniel; Sigrist, Jean-François (European Journal of Computational Mechanics, 2006)
The present paper deals with an homogenization method applied to a coupled fluidstructure problem. The method is exposed in details on a 2D elementary case for which the coupled fluid-structure formulation is developed. The proposed method leads to the modification of usual fluid-structure coupling operators in symmetric formulation. Its physical consistency is then demonstrated with a calculation of the cumulated modal masses for the coupled eigenmodes and an elementary validation is performed. The method can be applied for the seismic analysis of a nuclear reactor.